Vertical Relations Between Firms and Innovation: An Empirical Investigation of German Firms - Najib Harabi (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1997)
The surge in interfirm cooperative agreements can be seen as expressing a way for firms to respond to and to organize market failure, especially in technology markets. The incentives of firms to internalize activities are to avoid the disadvantages, or capitalize on the advantages, of imperfections or disequilibria in external mechanisms of resource allocations. The purpose of this paper is to investigate empirically the occurrence and importance of different modes of vertical relations between innovating firms, suppliers and users, using data from Germany. The analysis is based on a survey conducted by the "Center for European Economic Research" (Mannheim, Germany) among 3122 firms representing 378 different lines of business, mainly in the manufacturing sector. The main results can be summarized as follows: ? 84 % of all innovating firms responded that they have had R&D cooperation agreements with either suppliers or customers or both. This percentage is even higher (99 %) if we consider only those innovating firms that have also had formal R&D departments. The phenomenon of vertical R&D cooperation is therefore widespread among German firms. ? Informal exchange of technical knowledge was perceived as the most important mode of R&D cooperation between innovating firms on one hand and customers and suppliers on the other, followed by formal methods of cooperation such as joint development teams and contractual R&D cooperation. Joint ventures and direct R&D orders to either customers or suppliers were seen as the least important modes of vertical cooperation. ? The occurrence and importance of cooperative agreements between innovating firms, users and input suppliers vary across industries. ? Results of multivariate statistical analysis (correlation, principal components and cluster analysis) suggested that the various modes of R&D cooperation between innovating firms on one hand and customers and suppliers on the other could be reduced to two subgroups: the first one includes formal modes of cooperation, the second one includes only informal exchange of technical knowledge. On this basis patterns of cooperative agreements could be established for firms operating in different industries and for firms using different product and process technologies.
Keywords: 330; Innovation; Industrielle Forschung; Unternehmenskooperation; Vertikale Konzentration; Deutschland